Vector Control Drive Of Permanent Magnet Synchronous Motor Based Dsspace DS1103 Implementation - Cheok, Yong Seng; Zulkifilie, Ibrahim (2012)
This paper presented a vector controlled drives of permanent Magnet Synchronous Motor (PMSM) by using Proportional-Integral (PI) Speed controller based dSPACE implementation. The concept of vector control is applied to PMSM to obtain linear dynamics similar to that of a DC motor. The model consist of two control loops, hysteresis current controller is used for inner loop current control and PI controller for outer loop speed control. PI speed controller selected due to simplicity compare to fuzzy, neutral etc. to make sure dSPACE DS1103 successfully implemented. The PMSM vector control algorithm for a theoretical basic has been verified by experimental results and created a rapid control prototype environment by using MATLAB/ Simulink and the DS1103 DSP of dSPACE.